Porous Titanium Associated with CaP Coating: In Vivo and In Vitro Osteogenic Performance - Vasconcellos,Luana Marotta Reis de (2018)
This in vitro and in vivo study compared different topographies of Ti samples (dense, porosity of 30% and 40%) with or not CaP coating, prepared by powder metallurgy. Osteogenic cells from newborn rat calvaria were plated onto the samples and cell adhesion (24 hours), alkaline phosphatase activity (7 and 10 days) and mineralization nodules (14 days) were assessed. Sixteen rabbits were used for in vivo study. Each animal received three non-treated and three treated implants in the right or left tibia, respectively. Histometric evaluation of bone-implant contact (BIC) were assessed at 1, 2, 4 and 8 weeks. Metallographic analysis revealed porosities of 30% and 40%, with pore size ranging from 250 to 350 µm. Cell adhesion test and ALP revealed similar cell behavior, independently of topography and CaP coating (P > 0.05%). However, CaP coating combined with porosity of 40% influenced positively the mineralized matrix formation (P < 0.05%). CaP-coated implants showed higher BIC than non-CaP implants and BIC was different between the short (1 and 2 weeks) and long (4 and 8 weeks) healing periods (P < 0.05%). The results suggest that CaP coating combined with 40% porosity implants allowed greater osteogenesis in vitro and increased BIC in vivo.